2010
DOI: 10.1159/000276560
|View full text |Cite
|
Sign up to set email alerts
|

External Qi of Yan Xin Qigong Induces Apoptosis and Inhibits Migration and Invasion of Estrogen-Independent Breast Cancer Cells Through Suppression of Akt/NF-ĸB Signaling

Abstract: The antitumor effects of external Qi of Yan Xin Qigong (YXQ-EQ) have been widely described over the past three decades. To gain a better understanding of the mechanisms underlying YXQ-EQ’s antitumor effects, in the present study we investigated its effects on growth, migration, invasion and apoptosis of breast cancer cells and the underlying molecular mechanisms. We show that YXQ-EQ treatment caused a time-dependent reduction in viability, blocked clonogenic growth and induced apoptosis in estrogen-independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 46 publications
6
28
0
Order By: Relevance
“…There is also data available in the subject literature which shows an induction of apoptosis caused by qigong in different cells such as colorectal cancer cells [10,38] and [39]. In the presented study, upregulation of HSF-1 mRNA and antiapoptotic HSPA1A mRNA were also observed.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There is also data available in the subject literature which shows an induction of apoptosis caused by qigong in different cells such as colorectal cancer cells [10,38] and [39]. In the presented study, upregulation of HSF-1 mRNA and antiapoptotic HSPA1A mRNA were also observed.…”
Section: Discussionsupporting
confidence: 65%
“…It is also useful in reducing the symptoms of restless legs syndrome [8]. There are some reports on MBT in which the cytotoxic effect on cancer cells has been analysed, including the tumour cells of the pancreas [9] and breast cancer cells [10], as well usefulness in stuttering therapy [11].…”
Section: Introductionmentioning
confidence: 99%
“…The concept “External Qi of Qigong” refers to the technology and ability of “Qi deployment” therapy and health preservation of traditional Chinese medicine [4,5,6,7]. External Qi therapy has been used as one of the medical practices in China for thousands of years and is under management of the Chinese health authorities [8].…”
Section: Introductionmentioning
confidence: 99%
“…A great amount of YXQ-EQ experimental studies have shown significant effects of YXQ-EQ on structure and properties of DNA, RNA, protein and lipid molecules [10,14,15,16,17,18,19]. YXQ-EQ has been shown to regulate signaling pathways and gene expression in normal and malignant cells [4,5,6,7,18]. YXQ-EQ exerts potent cytotoxic effect on a variety of cancer cells and the underlying molecular mechanisms have recently begun to be addressed [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation